Behavior of thiosemicarbazones derived from some terpenones under acetylation conditions. Part II - Rouge, P.D. (2005)
Preparation of chiral heterocyclic compounds of the thiadiazoline types, starting from natural α,β-unsaturated and bicyclic terpenones is described. Stereochemical assignment of the compounds synthesized was performed by NMR spectroscopy and X-ray analysis. ©ARKAT.